Effect of steam and dry heat sterilization on the insertion and fracture torque of orthodontic miniscrews - Shiva Alavi; Farnaz Asadi; Seyed Amir Hossein Raji; Soroor Samie (Wolters Kluwer Medknow Publications, 2020)
Background: Titanium miniscrews are used at an ever-increasing rate to provide orthodontic anchorage. The aim of this study was to evaluate the mechanical performance of miniscrews after dry and steam sterilization. Materials and Methods: In this experimental study, a total of 72 miniscrews from two different manufacturers with a diameter of 1.6 mm and height of 8 mm were divided into six groups (n = 12). One group of screws from each manufacturer was considered as the control group; the second underwent steam sterilization; and the last group was subjected to dry sterilization. Insertion and fracture torques of each miniscrew were assessed by a torque tester. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests (P < 0.05). Results: For Jeil miniscrew, no statistically significant differences were detected between the steam-sterilized and control groups in their insertion torques (P > 0.05). There was a statistically significant difference between the steam sterilized, dry sterilized and control groups with respect to their fracture torque (P < 0.001). For Hubit miniscrew, there were no significant differences between steam sterilized, dry sterilized and control groups in their insertion torque (P > 0.05) and between steam sterilized and control groups with respect to their fracture torque (P > 0.05). There were significant differences in the mean values of insertion and fracture torques between the two different manufacturers (P < 0.001). Conclusion: Steam sterilization had no detrimental effects on torque values of miniscrews, but dry heat sterilization affected their mechanical properties.